The Impact Of Service Quality And Product Quality On Customer Loyalty And Its Impact On Repeats Order At Astra Credit Companies Makassar Branch - Abdul Rahman rahim; Andi Mappatompo; Simiati (Enrichment : Journal of Management, 2022)
This research aims to find out the influence of service quality, product quality on customer loyalty and repeat orders, the influence of customer loyalty on repeat orders and the influence of service quality, product quality on repeat orders through customer loyalty. The research background was based on inconsistencies in the results of previous research on the influence of service quality and product quality on customer loyalty which has impact on increasing repeat orders. The application of quantitative approach with data collection techniques through online questionnaires on 386 customers ACC Makassar Branch. Hypothesis testing deployed path analysis with the assistance of WarpPLS7 software. Test results showed that service quality, product quality has a significant impacton customer loyalty and repeat orders, service quality has a significant impact on repeat orders through customer loyalty, product quality has a significant positive impact on repeat orders. Through customer loyalty and customer loyalty has a significant impact on repeat orders . The test results showed that service quality is the most dominant variable impacting repeat orders in ACC Makassar Branch